Drug Hypersensitivity 2007
DOI: 10.1159/000104206
|View full text |Cite
|
Sign up to set email alerts
|

Clinic and Pathogenesis of Severe Bullous Skin Reactions: Stevens-Johnson Syndrome, Toxic Epidermal Necrolysis

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are the most severe forms of hypersensitivity reactions affecting the skin. They are best considered severity variants of a single disease on the basis of similar pathology (epidermal necrolysis), risk factors, causes and frequent progression from SJS to TEN in a few days. Most cases occur in patients with normal metabolic pathways, after taking for a mean of 2 weeks a normal dosage of a medication for the first time. A few 'high-risk' drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Among them, Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are the most severe forms of druginduced skin diseases and are now considered variants of the same disease. 2 SJS and TEN are rare diseases with a prevalence of 1 to 2 cases per million persons per year in white subjects and a mortality rate ranging from 2% to 10% in patients with SJS and 30% in patients with TEN. The most common feature of these diseases is the formation of subepidermal blisters and detachment of the epidermis, which appears as scalded skin.…”
mentioning
confidence: 99%
“…Among them, Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are the most severe forms of druginduced skin diseases and are now considered variants of the same disease. 2 SJS and TEN are rare diseases with a prevalence of 1 to 2 cases per million persons per year in white subjects and a mortality rate ranging from 2% to 10% in patients with SJS and 30% in patients with TEN. The most common feature of these diseases is the formation of subepidermal blisters and detachment of the epidermis, which appears as scalded skin.…”
mentioning
confidence: 99%
“…1,2 Nowadays SJS and TEN are best considered as severity variants of a single disease. 3,4 CDHR are considered type IV hypersensitivity reactions. Phenotypic diversity of the final expression of CDHR could be explained by the involvement of a variety of cytokines, inflammatory cells and regulatory mechanisms 5 whose precise nature is unknown so far.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,12,15 Moreover, published data show differences in gene expression intensity between benign and severe clinical entities. 11,13 In an attempt to get more insight into the molecular mechanisms involved in CDHR, we analysed the gene expression profiles of PBMCs during the acute phase and upon resolution of CDHR.…”
Section: Discussionmentioning
confidence: 99%
“…TEN and SJS require specialist care due to the epidermal detachment, with procedures paralleling those applied in the burns unit [ 21]. Systemic corticosteroids and intravenous immunoglobulins have been tried in SJS, but their use in TEN remains controversial and not recommended in the absence of randomized trial evidence [22]. The potential of intravenous immunoglobulins and other experimental treatments in the management of severe cutaneous adverse reactions is currently under investigation.…”
Section: Management Of Cutaneous Adverse Reactionsmentioning
confidence: 99%
“…Some authors have also found promising results with intravenous IgG in TEN patients [24], but other series were inconclusive. There is not enough evidence to support the use of IgG as part of the management strategy for these patients [22,25].…”
Section: Management Of Cutaneous Adverse Reactionsmentioning
confidence: 99%